Production of biofuels from sorghum. (May 2020) - Stamenković, Olivera S.; Siliveru, Kaliramesh; Veljković, Vlada B.; Banković-Ilić, Ivana B.; Tasić, Marija B.; Ciampitti, Ignacio A.; Đalović, Ivica G.; Mitrović, Petar M.; Sikora, Vladimir Š.; Prasad, P.V. Vara
Abstract: Sorghum is an important crop that serve multiple purposes as human food, animal feed, and bioenergy production. There are opportunities to produce different types of biofuels from sorghum-based biomass. Sorghum with its vast genetic resources can serve as bioenergy crop and not compete against the value of it as food and nutritional security crop. Bioenegy crops provides an opportunity for agriculture to be part of solution for energy and mitigation to climate change. This review provides detailed overview and current knowledge on the conversion of sorghum biomass (stalks, leaves, and grains) into liquid (bioethanol, biodiesel, and bio-oil), gas (biohydrogen, biogas, and syngas) and solid (biochar) biofuels. Progress made in the different sorghum-based biomass pretreatment and conversion processes including chemical, biochemical, thermochemical and biological processes (e.g. saccharification, fermentation, transesterification, hydrothermal liquefaction, pyrolysis, and gasification) are highlighted and described. In addition, several value-added products from sorghum gaining importance in biofuels production are summarized. Finally, the potential outlook on sorghum based biorefiners and potential for improving sorghum-based biofuel production is presented and discussed. The biorefinery concept offers a considerable scope for optimization of sorghum biomass utilization to produce biofuels and biochemicals. However, there is further need to clearly identify the best methods of pre-treatment, processing, and products from different sources. Sorghum with its high biomass production and multiple use has the potential to be key biofuel crop. Further research is needed to identify most efficient and cost effective processes to ensure the value of biofuel and other bioproducts from sorghum. A complete lifecycle analyses indicating the challenges and opportunities to enhance the efficiency, benefits, and challenges in different steps and finding solutions to overcome those challenges will be of prime importance. Strong collaboration between private and public sector researhcers and multidisciplinary teams will be required to develop a comprehensive biorefinery models. Graphical abstract: Overview of various methods of biofuel production from sorghum. Image 1 Highlights: Reviews current knowledge on various methods for biofuel production from sorghum. Sorghum oil, germ and dried grains with solubles are viable biodiesel feedstocks. Commercialization of thermochemical processes is more reliable than biological ones. Biologists should optimize the sorghum biomass properties for biofuel production. Biorefinery concept offers a scope for optimization of sorghum biomass utilization.